LONGITUDINAL MONITORING OF PERI-IMPLANT MICROCIRCULATION AS AN INDICATOR OF IMPLANT STABILITY AND PROSTHETIC SUCCESS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
By now time accumulated enough extensive experience in using the orthopedic method treatment of defects dental rows with support on implants. However, despite for certain achievements V region implantology, the incidence of complications remains high. When using prosthetics with the use of implants causes changes in the condition of the gums.